ASPECTS EPIDEMIO-CLINIQUES ET THERAPEUTIQUES DES PLAIES DE LA MAIN AU CENTRE HOSPITALIER UNIVERSITAIRE JOSEPH RAVOAHANGY ANDRIANAVALONA - Hanitrankasitrahana Amboarasarobidy, Rohimpitiavana; Veromboahangy, Randriambololona; Hoby Todisoa, Rasaomelinoro; Malinirina Fanjalalaina, Ralahy; Henri Jean Claude, Razafimahandry; Zo Lalaina Andrianina, Rabemazava Alexandrio; Gaëtan Duval, Solofomalala (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The traumatisms of the hand are frequent and require adequate specialized care. The purpose of our work was to determine the epidemiologicals, clinicals and therapeutics aspects of hand injuries at Joseph Ravoahangy Andrianavalona University Hospital. It was a descriptive retrospective study from January 2019 to december 2019. A total of 337 patients were included in the study. The population was mainly young adults, male (sex ratio 3.5). Hand workers were the most represented (48,07 %). The main cause of hand injuries was work accidents (49.3%). Treatment was orthopedic in 79.5% of cases. The adoption of measures aimed at prevention in work and improving accessibility to osteosynthesis will reduce the inherent complications of hand injuries.